Pola Interaksi Sosial Generasi Alpha di Kota Semarang pada Era Society 5.0 - Ahmad Fariz Alfarizi; Fredy Hermanto (Universitas Hamzanwadi, 2026)
Changes in the way the Alpha Generation socializes are not only seen in their closeness to gadgets, but also in how they move conversations between home, school, and digital spaces. This study aims to describe the social interaction patterns of the Alpha Generation in Semarang City in the Society 5.0 era from students’ perspectives, as well as to identify the factors that influence them. This research used a descriptive qualitative approach with a multisite case study design. The informants consisted of eight eighth-grade students from four schools with different characteristics: a public junior high school, a state Islamic junior high school, a national private junior high school, and an internationally oriented private junior high school. Data were collected through semi-structured interviews, observation, and documentation, then analyzed through data reduction, data display, conclusion drawing, and verification. The analysis used Soerjono Soekanto’s concept of social interaction, which places social contact and communication as the main requirements for social interaction. The findings show that the social interaction patterns of the Alpha Generation are hybrid. Direct social contact appears in family communication, peer interaction at school, group work, and conflict resolution, while indirect social contact occurs through WhatsApp, Instagram, TikTok, Discord, Roblox, and online games. Digital communication helps students maintain relationships and continue conversations after school, but it also creates misunderstandings because written messages do not fully show tone, expression, and intention. These findings indicate that technology expands students’ interaction spaces but does not replace their need for face-to-face communication.